Synthesis and Activity of Triazole-Adenosine Analogs as Protein Arginine Methyltransferase 5 Inhibitors - Tyler Brown; Mengtong Cao; Y. George Zheng (Molecules, 2022)
Protein arginine methyltransferase 5 (PRMT5) is an attractive molecular target in anticancer drug discovery due to its extensive involvement in transcriptional control, RNA processing, and other cellular pathways that are causally related to tumor initiation and progression. In recent years, various compounds have been screened or designed to target either the substrate- or cofactor-binding site of PRMT5. To expand the diversity of chemotypes for inhibitory binding to PRMT5 and other AdoMet-dependent methyltransferases, in this work, we designed a series of triazole-containing adenosine analogs aimed at targeting the cofactor-binding site of PRMT5. Triazole rings have commonly been utilized in drug discovery due to their ease of synthesis and functionalization as bioisosteres of amide bonds. Herein, we utilized the electronic properties of the triazole ring as a novel way to specifically target the cofactor-binding site of PRMT5. A total of about 30 compounds were synthesized using the modular alkyne-azide cycloaddition reaction. Biochemical tests showed that these compounds exhibited inhibitory activity of PRMT5 at varying degrees and several showed single micromolar potency, with clear selectivity for PRMT5 over PRMT1. Docking-based structural analysis showed that the triazole ring plays a key role in binding to the characteristic residue Phe327 in the active pocket of PRMT5, explaining the compounds’ selectivity for this type-II enzyme. Overall, this work provides new structure–activity relationship information on the design of AdoMet analogs for selective inhibition of PRMT5. Further structural optimization work will further improve the potency of the top leads.